How do different nitrogen application levels and irrigation practices impact biological nitrogen fixation and its distribution in paddy system? - Zhang, Yanhui; Hu, Tianlong; Wang, Hui; Jin, Haiyang; Liu, Qi; Lin, Zhibin; Liu, Benjuan; Liu, Hongtao; Chen, Zhe; Lin, Xinwu; Wang, Xiaojie; Ma, Jing; et al. (Plant and soil, 2021)
Background and aims Biological nitrogen fixation (BNF) in paddy systems is impacted by nitrogen application levels and irrigation strategies, but the extent to which these factors influence BNF and its distribution in soil and rice is largely unclear. This study investigates this influence. Methods An airtight, transparent growth chamber based 15 N-labelling system was used to investigate how different nitrogen application levels (0, 125, 187.5 and 250 kg N ha −1 ) and irrigation strategies (flooding irrigation or intermittent irrigation) impact the amount of BNF and its distribution in soil and rice. Results Nitrogen application at 125–250 kg N ha −1 reduced the amount of BNF by 81–86%. The inhibition effect of nitrogen application on BNF at a soil depth of 1–15 cm was greater than that at 0–1 cm. Relative to the continuous flooding irrigation, intermittent irrigation enhanced rice growth and promoted the transfer of fixed nitrogen from 0-1 cm soil layer to rice, but it did not change the total amount of BNF. Conclusions This study indicated that BNF supplied little nitrogen for rice production at the high nitrogen application levels, but the intermittent irrigation could promote utilization of biologically fixed nitrogen.